2007
DOI: 10.2106/jbjs.f.01466
|View full text |Cite
|
Sign up to set email alerts
|

Third-Generation Alumina-on-Alumina Ceramic Bearings in Cementless Total Hip Arthroplasty

Abstract: Cementless primary total hip prostheses with a third-generation alumina-on-alumina bearing showed very low wear and were associated with minimal osteolysis at the time of follow-up, at a minimum of five years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
70
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(86 citation statements)
references
References 30 publications
12
70
2
Order By: Relevance
“…The 5-year survivorship free from revision was 97.9% and this result is also comparable to the survival rate of 95.9% to 96.0% in intermediate-term studies using third-generation ceramics [8,23] and 97.6% in a short-term study using fourth-generation ceramics [15]. When new bearing materials are introduced, it is important to document patient-reported outcome and survivorship.…”
Section: Discussionsupporting
confidence: 57%
“…The 5-year survivorship free from revision was 97.9% and this result is also comparable to the survival rate of 95.9% to 96.0% in intermediate-term studies using third-generation ceramics [8,23] and 97.6% in a short-term study using fourth-generation ceramics [15]. When new bearing materials are introduced, it is important to document patient-reported outcome and survivorship.…”
Section: Discussionsupporting
confidence: 57%
“…The results of ceramic-on-ceramic bearings in patients who were older than 40 years have been reported [2,3,16,29,30], but few [6,15,23] have focused on the long-term results of ceramic-on-ceramic implants in patients younger than 20 years. In this series, we found the survivorship of ceramic-on-ceramic implants in adolescent patients was encouraging, averaging 90.3% at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramic-on-ceramic bearing couples have become an alternative to standard surface bearing couples (such as metal-on-polyethylene) because of decreased wear production and lower rates of osteolytic lesions compared with metal-on-conventional polyethylene [21]. The results of modern ceramic-on-ceramic bearings are available in patients younger than 60 years who have degenerative diseases [2,3,16,29,30], but few reports [6,15,23] have focused on patients younger than 20 years, who may be more likely to have high activity levels, perform sports activities, or engage in higher-demand workplace tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Early to intermediate clinical followup studies of 1-5 years with these newer ceramic bearings have reported low revision rates and few reports of wear, periprosthetic bone loss, or lysis [14,15,18,19,31]. Reported dislocation rates with ceramic bearings have been low (ie, 1.1% to 3%) [4,7].…”
Section: Introductionmentioning
confidence: 99%